Implementasi Pengelolaan Zakat Profesi - Finda Findiana (STEBI Global Mulia Cikarang, 2020)
Bekasi Regency, which has the largest industrial area in Southeast Asia with millions of workers, can be a potential for professional zakat collection. If this can be optimized, the zakat income obtained by BAZNAS Bekasi Regency will be larger. The purpose of this research was to determine the process of professional zakat management at the National Zakat Agency (BAZNAS) Bekasi Regency. The method used in this research is descriptive analytical method that describes the problem systematically, factually and accurately regarding the facts that occur in the field. The results of the research based on analytical descriptive analysis show that the process of planning, organizing and controlling of managing professional zakat in the BAZNAS Bekasi Regency is in a good category, while the implementation process is still not optimized for the incomplete collection of zakat on company workers in the Bekasi Regency area.